Syn-thrusting polygonal normal faults exposed in the hinge of the Cingoli anticline, northern Apennines, Italy - Petracchini, Lorenzo; Antonellini, Marco; Billi, Andrea; Scrocca, Davide (Frontiers in Earth Science, 2015)
The Cingoli arcuate anticline is part of the Apennines fold-thrust belt in Italy. The anticline involves sedimentary carbonate strata generally affected by syn-thrusting contractional structures such as bed-normal pressure solution seams, folds, and reverse faults. An exception is constituted by an outcrop in the anticline hinge, where sub-horizontal carbonate and chert beds are affected by joints and intraformational short normal faults. These faults are poorly-systematic and conceivably polygonal in map view. They cut through the carbonate beds while usually stop against the chert layers that are bent and extended along the faults themselves. At the fault tips, the displacement is generally transferred, via a lateral step, to an adjacent similar fault segment. The fault surfaces are often characterized by slickolites, greenish clayey residue, and micro-breccias including chert and carbonate clasts. Fault displacement is partly or largely accommodated by pressure solution. The faults, in effect, are usually accompanied by bed-parallel pressure solution seams in the two contractional quadrants located at the present or past fault tips. The pressure solution features fade away departing from the faults. This evidence and others are analytically explained with fault tip stress distributions. The faults are interpreted as polygonal normal faults syn-tectonically (syn-thrusting) nucleated in response to multi-directional stretching processes occurred at the Cingoli triple-folded anticline extrados. The faults then grew through a four-stage process: (1. stop) the faults stopped at the competent chert beds; (2. shrink) faulting produced shrinkage (pressure solution) of carbonate beds at the fault compressive tips; (3. shrink and step) the faults stepped laterally at the competent chert beds; (4. shatter) the chert beds were shattered along the fault surfaces. The case presented constitutes the first reported one of syn-thrusting non-diagenetic polygonal normal faults.